Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia - Rolando Robert; Dexter Jiunn Herng Lee; Kenneth Francis Rodrigues; Muhammad Ali Syed Hussein (2016)
Acropora is the most biologically diverse group of reef-building coral, and its richness peaks at the Indo-Malay-Philippine Archipelago, the centre of global coral reef biodiversity. In this paper, we describe the species richness of Acropora fauna of North Borneo, East Malaysia, based on review of literature and as corroborated by voucher specimens. Eighty-three species of Acropora are reported here; four species are literature based and 79 are supported by voucher specimens that were subsequently photographed. New records for North Borneo were recorded for 12 species, including Acropora suharsonoi Wallace 1994 that was previously thought to be confined to a few islands along Lombok Strait, Indonesia. The diversity of Acropora in North Borneo is comparable to that of Indonesia and the Philippines, despite the area’s smaller reef areas. This further reinforces its inclusion as part the global hotspot of coral biodiversity.